2005
DOI: 10.1097/01.brs.0000150505.59690.1b
|View full text |Cite
|
Sign up to set email alerts
|

Backpacks, Back Pain, Sagittal Spinal Curves and Trunk Alignment in Adolescents

Abstract: Backpack carrying, particularly asymmetrically, results in shift of upper trunk and shoulder and cervical lordosis, which furthermore seem to increase back pain in school period and holidays. Symmetric backpack carrying is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
88
3
10

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 36 publications
10
88
3
10
Order By: Relevance
“…The biomechanical effects of a backpack load alter the body CoM and result in forward lean 3) . This effect is similar to a forward head posture, which is the poor head posture commonly seen in neck pain patients 14,15) . In a forward head posture, the head is in front of the vertical line through the center of gravity of the body 16) .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The biomechanical effects of a backpack load alter the body CoM and result in forward lean 3) . This effect is similar to a forward head posture, which is the poor head posture commonly seen in neck pain patients 14,15) . In a forward head posture, the head is in front of the vertical line through the center of gravity of the body 16) .…”
Section: Discussionsupporting
confidence: 52%
“…Several studies have demonstrated that carrying a backpack results in a significant difference in the alignment of the head and spine and in sagittal shoulder posture. The stress while carrying a backpack straightens the neck, significantly decreasing the cervical curve 14) . The biomechanical effects of a backpack load alter the body CoM and result in forward lean 3) .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous studies [10,20,21,25,29] a cross-sectional study design was used for the weight and duration of carriage measurements. However in contrast to previous cross-sectional studies, the prevalence of schoolbagrelated musculoskeletal discomfort was established using a quasi-experimental pretest-posttest study design.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between schoolbag weight and musculoskeletal discomfort is not always clear as it has been found that the percent bodyweight (%BW) carried was both associated [5,19] and not associated [20,21] with musculoskeletal discomfort. Previous studies are mostly cross-sectional [10,20,21,25,29] and therefore have not been able to establish a dose-response relationship between schoolbag carriage and musculoskeletal discomfort. Additionally, they have not evaluated the discriminative ability of the proposed schoolbag weight cut-off values for identifying children with schoolbag-related discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, back pain is a current issue among young people with low back pain prevalence in adolescents measured between 20% to 72% [29,38]. Young people commonly use backpacks as they are an effective and most economical way of carrying weight, however, it has been proposed they can also be a significant contributing risk factor for dis-comfort, fatigue, muscle soreness and musculoskeletal pain especially low back pain [9,29,[47][48][49]57]. It has been speculated that backpacks may cause problems not only for the developing skeletal system but also for a mature spine as a developed spine is also sensitive to load [41,45].…”
Section: Introductionmentioning
confidence: 99%